Newer, Older, and Alternative Agents for the Eradication of Helicobacter pylori Infection: A Narrative Review - György Miklós Buzás; Péter Birinyi (Antibiotics, 2023)
Although discovered 40 years ago, Helicobacter pylori infection is still raising diagnostic and therapeutic problems today. The infection is currently managed based on statements in several guidelines, but implementing them in practice is a long process. Increasing antibiotic resistance and weak compliance of the patients limit the efficacy of eradication regimens, leaving much room for improvement. Third-generation proton pump inhibitors have added little to the results of the first two generations. Potassium-competitive acid blockers have a stronger and longer inhibitory action of acid secretion, increasing the intragastric pH. They obtained superior results in eradication when compared to proton pump inhibitors. Instead of innovative antibiotics, derivatives of existing antimicrobials were developed; some new fluoroquinolones and nitazoxanide seem promising in practice, but they are not recommended by the guidelines. Carbonic anhydrase inhibitors have both anti-secretory and bactericidal effects, and some researchers are expecting their revival in the treatment of infection. Capsules containing components of the eradication regimens have obtained excellent results, but are of limited availability. Probiotics, if containing bacteria with anti-Helicobacter pylori activity, may be useful, increasing the rates of eradication and lowering the prevalence and severity of the side effects.